The Influence of Financial Literacy and Investment Risk on Students’ Investment Interest: Perspective of Behavioral Finance Theory - Gede Aditya Putra; Putu Sukma Kurniawan; Luh Asri Savitri (LPPM Universitas Dhyana Pura, 2026)
This study aimed to examine the effect of financial literacy and investment risk on students’ investment interest in the Faculty of Economics. The study employed a quantitative approach and was carried out at the Universitas Pendidikan Ganesha. The sampling method used was Slovin’s formula, with the population consisting of fourth-semester students of the Faculty of Economics, Universitas Pendidikan Ganesha, resulting in a sample of 88 respondents. Data were collected using questionnaires and analyzed through multiple linear regression tests with the SPSS program. The results of this study indicate that both financial literacy and investment risk variables have a significant positive effect on investment interest. The findings of this research are expected to provide both theoretical and practical contributions to increasing students’ interest in investing.